Spontaneous Recurrent Seizures Mediated Cardiac Dysfunction via mTOR Pathway Upregulation: A Putative Target for SUDEP Management - Sharma, Supriya; Mazumder, Arindam G.; Rana, Anil K.; Patial, Vikram; Singh, Damanpreet (CNS & Neurological Disorders - Drug Targets, 2019)
Background: Alteration in electrophysiology, leading to cardiac dysfunction and subsequently a nontraumatic death is a complication of epilepsy known as “SUDEP” (Sudden Unexpected Death in Epilepsy). Aims: The present study was designed to understand the molecular changes and cardiac parameters during different phases of epileptogenesis in lithium-pilocarpine (Li-pilo) rat model of epilepsy. Methods: The animals were exposed to Li-pilo to induce Spontaneous Recurrent Seizures (SRS). Noninvasive blood pressure and electrocardiography was recorded at 7th, 28th and 75th day following pilocarpine administration, considered as latent, initial and late SRS phases, respectively. The serum biochemistry, cardiac histopathology, protein and mRNA expressions were studied, following electrocardiography on day 75. Results: The mean arterial pressure decreased during the latent phase, thereafter it progressively increased during the initial and the late SRS phases, as compared to the basal and the latent phase. Histopathological analysis of the heart sections indicated hypertrophy, degenerative changes and fibrous tissue deposition in epileptic animals, along with increased levels of lactate dehydrogenase and creatine kinase-MB in the serum. The expression of HIF-1α, phospho-S6, phospho-mTOR, TGF-β, collagen I and Na+/K+-ATPase α1 proteins, and mRNA levels of HIF-1α, mTOR, Rps6, Scn1b, Scn3b, Nav1.5 and TGF-β were increased in the cardiac tissue of epileptic animals, as compared to control. Conclusion: Our results conclusively showed that Li-pilo-induced SRS leads to cardiac dysfunction via mTOR pathway upregulation, thus suggested the regulatory control of mTOR pathway as a potential target for SUDEP management.
Keywords: fibrosis